THE IMPACT OF VOCABULARY KNOWLEDGE AND GRAMMAR MASTERY ON STUDENTS READING COMPREHENSION IN NARRATIVE TEXTS OF UNIVERSITY ENTRANCE EXAMS - Nur Ridwan, Revi (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study aims to analyze and test the truth of the hypothesis regarding the influence of Vocabulary and Grammar Mastery on Students' Reading Comprehension in Narrative Texts. The research hypotheses tested include: 1) The influence of Vocabulary and Grammar Mastery together on Reading Comprehension in Narrative Texts. 2) The influence of Vocabulary Mastery on Reading Comprehension in Narrative Texts. 3) The influence of Grammar on Reading Comprehension in Narrative Texts. The study was conducted using a survey method. The population was grade XI students of State Senior High Schools in Bandung City with a sample size of 60 students, with the sampling technique used being random sampling. The research instrument used was a multiple-choice test with 30 options that had been tested for normality with a sig. 0.200 > 0.05. Data analysis used multiple linear regression analysis. The results of the hypothesis testing obtained the following conclusions: 1) There is a significant influence of vocabulary and grammar mastery together on students' reading comprehension in narrative texts. This is evidenced by Fcount = 150.500 and Sig. 0.001 < 0.05. 2) There is a significant influence of vocabulary mastery on students' reading comprehension in narrative texts, this is evidenced by tcount = 8.517 and Sig. 0.001 <0.05. 3) There is a significant influence of grammar on students' reading comprehension in narrative texts, this is evidenced by tcount = 6.059 and Sig. 0.003 <0.05. The results of this study are useful for improving the quality of vocabulary mastery and improving English grammar at the high school level.